Monitoring the Change of Water Level and Its Effect on Water Quality in Sawa Lake, Southwest Iraq - Al-Tememi, Muhand. K.; Al-Mosawi, Walaa. M.; Abdulnabi, Zuhair Ali (Iraqi Journal of Science, 2019)
Sawa Lake is considered one of the distinct closed water systems located in the southwestern part of Iraq. In last years, the lake has suffered from a significant decrease in the water depth reached 1.5 m, thus the current study aims to monitor and analyse the change in water level, and identify causes and effect of this change on the lake hydrochemical properties by using analyzing cations and anions with the assistance of sub bottom profilers technique as well as obtained information from scientific diving. The results revealed that the lake had an equilibrium state between feed up and withdrawal water as well as evaporation during history. In spite of the high evaporation rates in the region, this equilibrium state made the lake doesn't dry up completely or become as a high salinity water system as brine lakes or as the Dead sea system. The equilibrium state is due to recycling and washing process of salt water by filtration and leakage under the bottom of the lake through the recharge site, so, there is a replacement of water, the decreasing in the lake level is not only attributed to evaporation factor, the main reason for this decreasing resulted in reducing the supply of Dammam aquifer, which is considered the main water supply effecting of the lake.